MANAGEMENT OF ENTERPRISES ON THE BASIS PROCESS APPROACH - Черчата, Анжела Олексіївна; Андрусів, Уляна Ярославівна; Зелінська, Галина Олексіївна; Михайлюк, Юрій Романович (Scientific Bulletin of Ivano-Frankivsk National Technical University of Oil and Gas (Series: Economics and Management in the Oil and Gas Industry), 2023)
The article is devoted to highlighting the role of optimization of business processes of the enterprise. The essence and significance of the business processes of the enterprise, in particular the construction one, as a tool for increasing the efficiency of its activity, were studied, the peculiarities of the introduction of the process approach were analyzed, taking into account the specifics of enterprises in the construction industry. Based on the systematization of the main interpretations of the concept of the business process, the article defined the essence of the business process as a sequence of actions aimed at achieving the goal within the framework of the general mission of the enterprise - the provision of quality services (production of products) to ensure a continuous current production process, which involves the management of flows on inputs and outputs, has a responsible executor and an economically measured result in conditions of uncertainty of the external environment and limited resources. It is justified that for effective process management, significant attention is paid to the optimization of business processes that ensure the activity of construction enterprises and are carried out with the aim of timely supply of material, financial, and informational resources at the input of the main processes and timely delivery of the newly created value of the product or service to the final consumer at the output. Application of the process approach and optimization of business processes have several advantages for enterprise management. They help to understand the full context and logic of actions of all interconnected processes, improve coordination and communication between departments and employees, reduce the time of tasks and increase the quality of products or services. In addition, the process approach and optimization of business processes contribute to continuous improvement, which allows the enterprise to be competitive in a constantly changing market environment. Based on a retrospective analysis, it was concluded that logistics and wide application of logistics management methods are used to solve similar problems. Since logistics management itself is crucial for the coordination of business processes taking place at the enterprise. Prospects for further research in this scientific direction are the development of a mechanism for assessing the business processes of a business entity, taking into account the specifics of its activity.